1985
DOI: 10.1159/000163299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Murine Tumor Necrosis Factor on Friend Erythroleukemic Cells

Abstract: Tumor necrosis inducing factor (TNF), a 140,000 molecular weight glycoprotein present in the serum of Corynebacterium parvum endotoxin-treated mice, was cytotoxic toward Friend virus-transformed erythroleukemic cells (FELC). These cells grow in culture as undifferentiated pro-erythroblasts but can be induced to differentiate in a limited fashion along the erythroid pathway to orthochromatic normoblasts by various agents such as dimethylsulfoxide (DMSO). Partially and highly purified preparations of TNF were cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
1

Year Published

1985
1985
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
(16 reference statements)
2
9
1
Order By: Relevance
“…In contrast. TNF under identical conditions produced the same results following 4-hour exposure that was obtained only after 12 h of incubation with NHG-I [15].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In contrast. TNF under identical conditions produced the same results following 4-hour exposure that was obtained only after 12 h of incubation with NHG-I [15].…”
Section: Resultssupporting
confidence: 76%
“…Koo [9] has character ized the growth inhibitory activity associated with an a 2-macroglobulin fraction from mice and lately [10] described a cytotoxic effect upon various human and murine tumor cell lines of a human < X 2-macroglobulin. We have recently studied the effect of TNF upon erythroleukemic cells [13,15] and here report the results of similar studies using NHG-I.…”
Section: Introductionmentioning
confidence: 88%
“…Cells of the mononuclear phagocyte lineages are the primary source of TNF-a, but it is now known that many other cell types produce this cytokine, including lymphocytes, mast cells, and even fibroblasts ( 15). TNF is involved in various pathological and physiological situations, and it is implicated alone or in association with other cytokines such as interleukin (1L)-I , IL-6, and interferons in the pathogenesis of different diseases such as septic shock and cerebral malaria and autoimmune diseases such as rheumatoid arthritis (17,10,7).Various assays have been reported for the measurement of TNF cytotoxicity (1,3,5,8,9,(11)(12)(13)16 Recombinant TNF The recombinant human TNF-a used for these assays was produced in our laboratory (14). This purified TNF-a had a specific activity of 10' units per milligram as determined by the standard T N F assay of Aggarwal and Kohr ( 1 ).…”
mentioning
confidence: 99%
“…Various assays have been reported for the measurement of TNF cytotoxicity (1,3,5,8,9,(11)(12)(13)16 Recombinant TNF The recombinant human TNF-a used for these assays was produced in our laboratory (14). This purified TNF-a had a specific activity of 10' units per milligram as determined by the standard T N F assay of Aggarwal and Kohr ( 1 ).…”
mentioning
confidence: 99%
“…We have recently shown that tuftsin stimulates the production of tumour necrosis factor (TNF) (Wleklik et al, 1985), which is known to be responsible for the necrosis of various tumours (Maranaska et al, 1984). This may be of special interest as Suyama et al (1985) have shown that TNF is cytotoxic towards FLV-transformed erythroleukaemic cells.…”
Section: Short Communicationmentioning
confidence: 99%